Antibacterial intraosseous implant surface coating that responds to changes in the bacterial microenvironment - Bai, Xin; Yu, Jiawei; Xiao, Jie; Wang, Yanping; Li, Zhe; Wang, Hao (Frontiers in Bioengineering and Biotechnology, 2023)
Bone implant-associated infection is one of the most challenging problems encountered by orthopedic surgeons. There is considerable interest in the development of drug-loaded antibacterial coatings for the surfaces of metal implants. However, it is difficult to achieve the stable local release of an effective drug dose for many antibacterial coatings. In the present study, analyses of the thickness and water contact angle of multiple layers confirmed the successful assembly of multilamellar membrane structures. Measurement of the zone of bacterial inhibition indicated gradual degradation of the (montmorillonite [MMT]/hyaluronic acid [HA])10 multilamellar film structure with concentration-dependent degradation during incubation with hyaluronidase solution and Staphylococcus aureus. In vivo results resembled the in vitro results. Overall, the findings confirm that the (MMT/HA-rifampicin)10 multilamellar film structure exhibits good antibacterial properties and excellent biocompatibility. Further studies of the clinical potential of the antibacterial coating prepared in this experiment are warranted.